Medical professionalism - Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2019)
Medical profession is a social contract between doctor and society in medical practice. It follows the business principle with human touch for a dignified medical profession. Proficiency, competency, evidences and set standards in education, training and practice are the key features of medical profession. Keywords: business principle, doctor, medical profession, regulation, society